Corporate governance of Chinese publicly listed companies - Gu, Wei (2013)
Agency theory suggests that problems will arise when there is a separation of ownership and control in firms. According to the literature, the main agency problem under a diffused ownership structure is likely to be the conflict of interests between managers and shareholders, whereas the central agency problem under a concentrated ownership structure is probably the exploitation of minority shareholders' interests by controlling shareholders. In the case of Chinese enterprises, such problems are even more complicated, as the government acts as both the regulator and player in the markets.